Strategi Dakwah DKM Jami Al-Huda Kepada Masyarakat Urban dan Dampaknya terhadap Pemahaman Agama di Desa Hegar Wangi - Randi Wahyu Rahmadan; Komarudin Shaleh; Nandang HMZ (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. The Purpose of this study was to find out the DKM Preaching strategy of the jami Alhuda mosque towards urban communities whi are rather difficult to understand the contents of the Friday sermon message using Sundanese language which influences their religious understanding, thus making urban people view that a mosque is in the midst of a rural community environment. Hegarwangi is merely a place of worship. This research uses a descriptive study method with a qualitative approach. Methods of data collection is done by means of observation, interviews, documentation. The stages of data analysis in the study, namely data collection, data reduction, data presentation and drawing conclusions. The result of this study show that the Jami Alhuda mosque in its sermons is not effective for urban people, and urban people’s religious understanding does not develop through the Friday sermon delivered by the jami Alhuda mosque preacher in hegarwangi Village. Abstract. The Purpose of this study was to find out the DKM Preaching strategy of the jami Alhuda mosque towards urban communities whi are rather difficult to understand the contents of the Friday sermon message using Sundanese language which influences their religious understanding, thus making urban people view that a mosque is in the midst of a rural community environment. Hegarwangi is merely a place of worship. This research uses a descriptive study method with a qualitative approach. Methods of data collection is done by means of observation, interviews, documentation. The stages of data analysis in the study, namely data collection, data reduction, data presentation and drawing conclusions. The result of this study show that the Jami Alhuda mosque in its sermons is not effective for urban people, and urban people’s religious understanding does not develop through the Friday sermon delivered by the jami Alhuda mosque preacher in hegarwangi Village.